Countering Terrorist Narratives: Assessing the Efficacy and Mechanisms of Change in Counter-narrative Strategies - Carthy, S. L. (Terrorism and political violence, 2023)
This study presents the findings of a laboratory-based experiment testing hypothesised processes implicated in the prevention of violent radicalisation through counter-narratives. The central aims of the study were to contribute to counter-narrative theory, whilst highlighting the value of experimental methodologies that can be deployed in this area of scientific enquiry. Two counter-narrative strategies were evaluated against a dominant terrorist narrative. Considering the role of cognition in the processing of narrative-related information, participants’ (n = 150) Cognitive Reflection and Need for Cognition were measured before they were randomly assigned to a narrative that legitimized terrorist violence, one of two counter-narratives, or a control. Returning autonomy to the target by having them actively counter terrorist rhetoric themselves was found to be more effective than offering generic counter-narratives. Notwithstanding the challenges and limitations associated with measuring violent radicalization-related constructs, the findings of the experiment demonstrate the extent to which individuals vary in their susceptibility to violent, terrorist narratives, as well as attempts to counter them.